PENGARUH MODAL, TEKNOLOGI, HARGA DAN PRODUKSI TERHADAP PENDAPATAN PENGRAJIN KAIN ENDEK DI KOTA DENPASAR - Septia, Cindy; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Endek fabric in Denpasar City one of Creative Industries support the economic income community. It is known the economic conditions of people in Bali Province influenced by the tourism sector and industries the potential of the trade sector is dominated by the Small and Medium Enterprises (UMKM). Few years there was a decline in income. Factors have caused in business income, one of which is the lack of optimal sources of capital and utilization of human resources. Purpose this study was to determine several factors such as capital, technology, price and production affect the income of Endek fabric craftsmen in Denpasar. Used 37 units of Endek fabric craftsmen for respondents. Analysis used Multiple Linear Regression. The results showed; capital, technology, price and production variables have a simultaneous and significant effect. Partially, capital, technology and production variables have a positive and significant effect, but the price variable does not significantly influence the income of Endek fabric craftsmen in Denpasar. This study recommends that Endek fabric craftsmen more maximize production factors, capital and technology so that the impact on the business income of the craftsmen themselves, so as to prosper the owners and workers. Keywords: Capital, Technology, Price, Production, Business Income.